Ответы и объяснения

2014-01-07T14:43:13+00:00
8) б) cos² (π/2  + x) - cos² (2π + x) =  \frac{ \sqrt{3} }{2}
по формулам приведения:
cos² (π/2 + x) = sin²x
cos² (2π + x) = cos²x
sin²x - cos²x =  \frac{ \sqrt{3} }{2}
- cos2x =  \frac{ \sqrt{3} }{2}
cos2x = - \frac{ \sqrt{3} }{2}
2x = +- 5π/6 + 2πn
x = +- 5π/12 + πn
в) cos⁴x - sin⁴x = - \frac{ \sqrt{3} }{2}
(cos²x - sin²x) (cos²x + sin²x) = -  \frac{ \sqrt{3} }{2}
cos2x = - \frac{ \sqrt{3} }{2}
x=
+- 5π/12 + πn
д) sin2x +  \sqrt{3} cos2x = 0
tg2x +  \sqrt{3} = 0
tg2x = - \sqrt{3}
2x = -π/3 + πn
x = -π/6 + πn/2